Supply Chain and Value Chain dalam Pemasaran Kain dan Produk Turunannya di Kota Subulussalam - Ariel Miansyah; Annio Indah Lestari Nasution (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to analyze the factors that influence the supply chain and value chain in the marketing of fabrics and their derivative products in the City of Subulussalam using qualitative methods. This research was conducted by collecting data through in-depth interviews and direct field observations. Respondents in this study were manufacturers of fabrics and their derivative products in the city of Subulussalam. The results of the study show that the supply chain in the marketing of fabrics and their derivatives affects product quality, production speed, fulfillment of consumer demand, reduction of production costs, and product innovation. Therefore, good supply chain management in the marketing of fabrics and their derivatives can improve the quality of these fabrics and their derivatives. While the value chain in cloth marketing affects product quality, raw material selection, production efficiency, environmental sustainability, and relationships between stakeholders in cloth marketing. Good value chain management in fabric marketing can improve fabric product quality, production efficiency, and environmental sustainability. In addition, good value damage management can also improve. This research is expected to contribute to the producers of fabrics and their derivative products in the City of Subulussalam in facing challenges and taking advantage of opportunities in the fabric industry and their derivative products. This research can also be used as a reference for further research on supply chains and value chains in the fabric industry and its derivative products in other regions in Indonesia.